Rational solutions for the nonlocal sixth-order nonlinear Schrödinger equation. (October 2018) - Liu, De-Yin; Sun, Wen-Rong
Abstract: We derive the nonlocal sixth-order nonlinear Schrödinger (NLS) equation which admits rational solutions. Through the Lax pair, we prove the integrability of the nonlocal NLS equation. Furthermore, with the Darboux transformation, analytic rational solutions up to the second order are explicitly given.